Predictors and Mortality of Rapidly Progressive Interstitial Lung Disease in Patients With Idiopathic Inflammatory Myopathy: A Series of 474 Patients - Li, Yuhui; Gao, Xiaojuan; Li, Yimin; Jia, Xiaohui; Zhang, Xuewu; Xu, Yan; Gan, Yuzhou; Li, Shiming; Chen, Renli; He, Jing; Sun, Xiaolin (Frontiers in Medicine, 2020)
Objective: This study was conducted to identify the characteristics and prognosis of rapidly progressive interstitial lung disease (RP-ILD) in idiopathic inflammatory myopathy (IIM) and to assess the predictors for poor survival of RP-ILD in IIM. Methods: A total of 474 patients with IIM were enrolled retrospectively according to medical records from People’s Hospital Peking University. Clinical and laboratory characteristics recorded at the diagnosis of patients with RP-ILD and chronic ILD (C-ILD) were compared. The Kaplan-Meier estimator and univariate and multivariate analyses were used for data analysis. Results: ILD was identified in 65% (308/474) of patients with IIM. Patients with ILD were classified into two groups based on lung features: RP-ILD (38%, 117/308) and C-ILD (62%, 191/308). RP-ILD resulted in significantly high mortality in IIM compared with C-ILD (27.4% vs. 7.9%, P<0.05). In this study, by comparison between IIM patients with and without RP-ILD, a list of initial predictors for RP-ILD development were identified, which included older age at onset, decreased peripheral lymphocytes, skin involvement (periungual erythema, skin ulceration and subcutaneous/mediastinal emphysema), presence of anti-MDA5 antibody, serum tumor markers, etc. Further multivariate Cox proportional hazards model analysis identified that anti-MDA5 positivity was an independent risk factor for mortality due to RP-ILD (P<0.05), and lymphocytes < 30% in BALF might also associate with poor survival of myositis-associated RP-ILD (P<0.05). Conclusion: Our study shows that RP-ILD results in increased mortality in IIM. Anti-MDA5 positivity and lower lymphocyte ratio in BALF might be the predictive factor of mortality due to RP-ILD.